Histomorphological transformation from non-small cell lung carcinoma to small cell lung carcinoma after targeted therapy or immunotherapy: A report of two cases - Liu, Hao; Chen, Li-Hong; Zhang, Zhi-Hui; Wang, Ning; Zhuang, Si-Hui; Chen, Hao; Du, Jin; Pang, Li-Juan; Qi, Yan (Frontiers in Oncology, 2022)
Molecular targeting and immunotherapy provide durable responses for advanced lung cancer clinical therapy in many patients. However, the mechanisms of occurrence of progressive disease and resistance to targeted therapy and immunotherapy have not been elucidated. Herein, we report two cases of small cell transformation of non-small cell lung cancer (NSCLC) after targeted therapy or immunotherapy. The first case was a 63-year-old female patient presenting with cough and expectoration. Left lung invasive adenocarcinoma was diagnosed after left lung tumor biopsy. After epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) targeted therapy for almost 2 years, disease progression and symptom aggravation were observed. Pathological and immunohistochemical staining results after biopsy revealed small cell lung cancer (SCLC). The second case was a 75-year-old male patient diagnosed with stage IV squamous cell carcinoma of the lung, who received carboplatin/paclitaxel adjuvant chemotherapy and pembrolizumab treatment with partial response. Disease progression and metastasis occurred within 15 cycles of immunotherapy. Computed tomography revealed a lower left lung tumor. Cytological examination of lung lavage fluid and biopsy under thoracoscope revealed SCLC. In conclusion, histological transformation to SCLC is a potential mechanism of NSCLC resistance to targeted therapy or immunotherapy. During treatment, clinicians should monitor serum tumor markers or genome sequencing, particularly in patients with disease progression, as this may be beneficial for early detection of SCLC transformation. Repeated biopsy can be performed if necessary, and the therapeutic regimen can be adjusted in a timely manner according to the results of molecular pathological tests for personalization and whole-process management.